Development of a models of interpersonal competencies as a complex system - Blažinić, Boris (Array, 2020)
Competencies represent a dynamic combination of cognitive and metacognitive skills, knowledge and understanding, interpersonal and practical skills, and ethical values. Since there are many entities, as well as many activities between entities, according to system theory, the whole system belongs to complex systems. The paper develops a conceptual and computational model of interpersonal competences for the process of optimization and methodology design, using simulation modeling. The developed model enables: faster data collection, more accurate results, avoiding human error in data entry and processing, survey time can be measured and more easily restricted, NMAR (Not Missing at Random) data is avoided and socially desirable responses are more easily avoided.